FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2013-2015 - Hastuti, Rini Tri (Jurnal Ekonomi, 2017)
The purpose of this research is to reexamine the factors allegedly effecttoincome smoothing, whiches firm size, profitability, financial leverage, institutional ownership. The sample of this study consisted of 59 manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2013 until 2015. To determine the status of grading company and not a profit grader used Eckel index. As for answering research hypothesis used Logistic Regression analysis tools. The results of this study concludes that income smoothing taken by the company to go public in the Indonesia Stock Exchange (IDX). Multivariate testing using the Logistic Regression showed thatfirm size, profitability, financial leverage has significant effect on income smoothing. While, the variable institutional ownership had no significant effect on income smoothing.